Intracranial Myxoid Mesenchymal Tumor/Myxoid Subtype Angiomatous Fibrous Histiocytoma: Diagnostic and Prognostic Challenges. Issue 1 (24th September 2020) - Domingo, Ricardo A; Vivas-Buitrago, Tito; Jentoft, Mark; Quinones-Hinojosa, Alfredo
ABSTRACT: BACKGROUND AND IMPORTANCE: In the setting of intracranial neoplasms, EWSR1-cAMP Response Element-Binding Protein (CREB) transcription factor family fusions have been described in myxoid mesenchymal tumors, extremely rare entities with a close histopathologic and immunologic resemblance to myxoid subtype angiomatoid fibrous histiocytomas (AFH). Controversy exists on whether these central nervous system lesions are a subtype of myxoid AFH or a completely separate entity, which entitles a distinct clinical behavior and, consequently, a different approach to management. Upon review of the literature, only 14 cases of intracranial tumors harboring an EWSR1-CREB family fusion were identified, with only 3 cases presenting in middle-aged adults, none of which reported an EWSR1-CREM fusion mutation. Significant variability in reported radiographic and histopathological characteristics, as well as in clinical outcomes, was noted. Their similarity with other soft tissue tumors, added to the scarce information on its clinical behavior, represents a great diagnostic and therapeutic challenge to the treating physician. CLINICAL PRESENTATION: We present a rare case of EWSR1-CREM mutated intracranial myxoid mesenchymal tumor/myxoid subtype AFH presenting as persistent headaches in a 36-yr-old woman with radiographic evidence of rapid growth and extensive vasogenic edema, for which she underwent surgical resection. CONCLUSION: This represents a unique case of EWSR1-CREM mutated intracranial myxoid mesenchymal tumor presenting in adulthood, with evidence of aggressive behavior.